Atrial Fibrillation Is Associated with a Marker of Endothelial Function and Oxidative Stress in Patients with Acute Myocardial Infarction - Stamboul, Karim; Lorin, Julie; Lorgis, Luc; Guenancia, Charles; Beer, Jean-Claude; Touzery, Claude; Rochette, Luc; Vergely, Catherine; Cottin, Yves; Zeller, Marianne (PloS one, 2015)
Atrial fibrillation (AF), whether silent or symptomatic, is a frequent and severe complication of acute myocardial infarction (AMI). Asymmetric dimethylarginine (ADMA), an endogenous eNOS inhibitor, is a risk factor for endothelial dysfunction. We addressed the relationship between ADMA plasma levels and AF occurrence in AMI. 273 patients hospitalized for AMI were included. Continuous electrocardiographic monitoring (CEM) ≥48 hours was recorded and ADMA was measured by High Performance Liquid Chromatography on admission blood sample. The incidence of silent and symptomatic AF was 39(14%) and 29 (11%), respectively. AF patients were markedly older than patients without AF (≈ 20 y). There was a trend towards higher ADMA levels in patients with symptomatic AF than in patients with silent AF or no AF (0.53 vs 0.49 and 0.49 μmol/L, respectively, p = 0.18,). After matching on age, we found that patients with symptomatic AF had a higher heart rate on admission and a higher rate of patients with LV dysfunction (28% vs. 3%, p = 0.025). Patients who developed symptomatic AF had a higher ADMA level than patients without AF (0.53 vs. 0.43 μmol/L; p = 0.001). Multivariate logistic regression analysis to estimate symptomatic AF occurrence showed that ADMA was independently associated with symptomatic AF (OR: 2.46 [1.21-5.00], p = 0.013) beyond history of AF, LVEF<40% and elevated HR. We show that high ADMA level is associated with the occurrence of AF. Although no causative role can be concluded from our observational study, our work further supports the hypothesis that endothelial dysfunction is involved in the pathogenesis of AF in AMI.